Triblock polyester thermoplastic elastomers with semi-aromatic polymer end blocks by ring-opening copolymerization - Gregory,GL; Sulley,GS; Carrodeguas,LP; Chen,TTD; Santmarti,A; Terrill,NJ; Lee,K-Y; Williams,CK (Chemical Science, 2020)
Thermoplastic elastomers benefit from high elasticity and straightforward (re)processability; they are widely used across a multitude of sectors. Currently, the majority derive from oil, do not degrade or undergo chemical recycling. Here a new series of ABA triblock polyesters are synthesized and show high-performances as degradable thermoplastic elastomers; their composition is poly(cyclohexene-alt-phthalate)-b-poly(ε-decalactone)-b-poly(cyclohexene-alt-phthalate) PE–PDL–PE. The synthesis is accomplished using a zinc(II)/magnesium(II) catalyst, in a one-pot procedure where ε-decalactone ring-opening polymerization yielding dihydroxyl telechelic poly(ε-decalatone) (PDL, soft-block) occurs first and, then, addition of phthalic anhydride/cyclohexene oxide ring-opening copolymerization delivers semi-aromatic polyester (PE, hard-block) end-blocks. The block compositions are straightforward to control, from the initial monomer stoichiometry, and conversions are high (85–98%). Two series of polyesters are prepared: (1) TBPE-1 to TBPE-5 feature an equivalent hard-block volume fraction (fhard = 0.4) and variable molar masses 40–100 kg mol−1; (2) TBPE-5 to TBPE-9 feature equivalent molar masses (∼100 kg mol−1) and variable hard-block volume fractions (0.12 < fhard < 0.4). Polymers are characterized using spectroscopies, size-exclusion chromatography (SEC), thermal gravimetric analysis (TGA), differential scanning calorimetry (DSC) and dynamic mechanical thermal analysis (DMTA). They are amorphous, with two glass transition temperatures (∼−51 °C for PDL; +138 °C for PE), and block phase separation is confirmed using small angle X-ray scattering (SAXS). Tensile mechanical performances reveal thermoplastic elastomers (fhard < 0.4 and N > 1300) with linear stress–strain relationships, high ultimate tensile strengths (σb = 1–5 MPa), very high elongations at break (&ep